Unruly media YouTube, music video, and the new digital cinema - Vernallis, Carol (Oxford University Press, 2013)
'Unruly Media' is the first book to account for the current audiovisual landscape across media and platform. It includes new theoretical models and close readings of current media as well as the oeuvre of popular and influential directors